Effective Collaboration of Entrepreneurial Teams-Implications for Entrepreneurial Education - Beata Krawczyk-Bryłka; Katarzyna Stankiewicz; Paweł Ziemiański; Michał T. Tomczak (MDPI AG, 2020)
In the situation of a permanent change and increased competition, business ventures are more and more often undertaken not by individuals but by entrepreneurial teams. The main aim of this paper is to examine the team principles implemented by effective entrepreneurial teams and how they differ in nascent and established teams. We also focused on the relationship between the implementation of these rules by entrepreneurial team members and their evaluation of venture performance and personal satisfaction. The quantitative method was used: a list of nine items describing the principles important for the entrepreneurial teams' collaboration was included in a questionnaire conducted in a group of 106 Polish entrepreneurs who run their businesses as members of entrepreneurial teams. The results of the research showed that all the collaboration principles included in the prepared scale are implemented by the tested entrepreneurial teams; in the case of two particular items, the obtained scores were higher in nascent teams. The correlation between principle implementation and venture performance as well as the correlation between principle implementation and entrepreneurs' professional satisfaction was confirmed. In addition, the goal was to emphasize the importance of the entrepreneurial team's collaboration due to its effectiveness, and propose the prepared scale as a tool for entrepreneurial reflective learning. Finally, statements by members of two entrepreneurial teams concerning team collaboration are presented to deliver case studies that can be used during entrepreneurship courses.